The dynamics of socio-psychological adaptation of adolescents engaged in artistic creativity - Chernaya Y. S., Shklyaruk S. P. (Humanitarian, 2017)
this article presents a study of the dynamics of socio-psychological adaptation in adolescents during the course of pictorial arts. 60 teenagers aged 13 to 17 years have been participating in a longitudinal study for three years, systematically involved and not involved in pictorial art. It has been found that the creative adolescents have lower level of neuro-psychological adaptation and higher level of subjective feelings of loneliness than non-creative adolescents. But creative teenagers have significantly higher self-esteem, level of aspiration and satisfaction in achieving success and lower anxiety in relationships with adults. The influence of the creative group reflected on such personal qualities as: self-confidence, credibility among peers, ability to do things with their hands, social identity, loneliness, frustration needs in achieving success, problems and fears in relations with adults. The personal characteristics of creative adolescents have been identified. These characteristics distinguish them from others teenagers, and the effect of the creative group and creative activity indirectly on the personal qualities of adolescents.
Keywords: творчество; адаптация; самооценка; идентичность; творческая группа; creativity; adaptation; self-esteem; identity; кризис подросткового возраста; чувство одиночества; crisis of adolescence; creative team; feeling of loneliness